Analisis kepuasan pemustaka terhadap layanan perpustakaan dan pusat layanan digital Universitas Muhammadiyah Surakarta selama masa pasca pandemi - Hidayat, Mansur; Utami, Kurnia; Pujianti, Sapta; Nisa, Maria Husnun (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
In organizing learning and teaching activities in higher education, the library is one of the main factors in realizing the chess dharma of higher education. The Covid 19 pandemic that has hit the world has slowly but surely experienced a decline, so that all public services have gradually returned to normal, one of which is the Library Service and Digital Service Center of the Muhammadiyah University of Surakarta (UMS). This research uses descriptive quantitative methods to determine the level of user satisfaction. The results of this research as a whole are in the "very much in line with expectations" category. The performance of library staff in serving users is the highest component, followed by guarantee of service received by users, library facilities and infrastructure, availability of library collections and the lowest is the accessibility of library services.